Kreativitas Mahasiswa Fisika dalam Mendesain Produk Materi Medan dan Gaya Magnet (UPEJ Unnes Physics Education Journal, 2019)
This research aims to know the students ' creativity and factors influencing creativity. The data used in this study that is the result of a creative product evaluation form design and interview. Data analysis techniques used to use a descriptive quantitative analysis approach. The results of data analysis it was concluded that the creativity of the students in physics are divided into three categories, namely high, medium, low details: creativity category